2013
DOI: 10.1021/mz400407m
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Strength at Immiscible Polymer Interfaces

Abstract: Thermal welding of polymer-polymer interfaces is important for integrating polymeric elements into devices. When two different polymers are joined, the strength of the weld depends critically on the degree of immiscibility. We perform large-scale molecular dynamics simulations of the structure-strength relation at immiscible polymer interfaces. Our simulations show that immiscibility arrests interdiffusion and limits the equilibrium interfacial width. Even for weakly immiscible films, the narrow interface is u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(94 citation statements)
references
References 39 publications
11
80
0
Order By: Relevance
“…31 A simple quartic potential with the same equilibrium spacing was used in the mechanical tests since chain scission plays an essential role in failure. As in past simulations, 6,7,18,30,32 the breaking force for the quartic potential, 240u 0 /a, is 100 times higher than that for the intermolecular LJ potential. This ratio is consistent with experimental estimates.…”
Section: Simulation Model and Methodologysupporting
confidence: 73%
See 3 more Smart Citations
“…31 A simple quartic potential with the same equilibrium spacing was used in the mechanical tests since chain scission plays an essential role in failure. As in past simulations, 6,7,18,30,32 the breaking force for the quartic potential, 240u 0 /a, is 100 times higher than that for the intermolecular LJ potential. This ratio is consistent with experimental estimates.…”
Section: Simulation Model and Methodologysupporting
confidence: 73%
“…To limit excluded volume effects, we use a modification of the original PPA algorithm where the diameter of repulsive interactions between chains is then reduced by a factor of four and the contour is minimized again. 6,18,45 The resulting configuration is a network of primitive paths for each chain.…”
Section: Simulation Model and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…[ 23,25 ] However, numerous studies have shown that the adhesion between poorly miscible polymers, such as PGMA-PAS, or use of short linkers (ethylene diamine) are generally weak due to poor chain diffusion and localized stress concentration. [ 29,[42][43][44] The symmetric PGMA-PGMA interface employed in our studies enables diffusion and chain entanglement of polymer chains between the fi lms, which are important factors to realize higher adhesion energies. [ 40 ] Together with the crosslinking ability of iCVD PGMA, moderate thermal treatments enabled us to tailor the crack-propagation interface in bonded substrates.…”
Section: Transitions In Film Adhesive Properties Characterized By Posmentioning
confidence: 99%